2015
DOI: 10.3923/ijar.2016.32.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fertilizer Application and Plant Density on Physiological Aspect and Yield of Taro (Colocasia esculenta (L.) Schott var. Antiquorum)

Abstract: A research was conducted to study the effect of nitrogen and potassium (NK) fertilizers and plant density on the growth and yield of taro (Colocasia esculenta (L.) Schott var. Antiquorum). The field experiment was carried out at Brawijaya University experimental field station located at Jatikerto, Malang, Indonesia. The experimental treatments consist of three plant density (18,000, 24,000 and 30,000 haG

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
0
7
1
5
Order By: Relevance
“…Total fruit fresh weight obtained at 281 kg N ha -1 rates showed an increase of 20.19% over that of 0 kg N ha -1 rate, whereas, increasing P rates from 0 to 269.6 kg ha -1 , increase fresh fruit weight by 68.22%; a further increase P application up to 404.4 kg ha -1 decreased fruit fresh weight by 11.21 percent. On contrary, the results obtained from this study is higher than the reported value of 127.04 kg N ha -1 and 65 kg P ha -1 with fruit fresh weight of 16.72 t ha -1 [26]. The observed disparity between the results could be explained on the basis of the soil fertility difference and the environmental conditions upon which the plant was grown.…”
Section: Economic Evaluationcontrasting
confidence: 97%
“…Total fruit fresh weight obtained at 281 kg N ha -1 rates showed an increase of 20.19% over that of 0 kg N ha -1 rate, whereas, increasing P rates from 0 to 269.6 kg ha -1 , increase fresh fruit weight by 68.22%; a further increase P application up to 404.4 kg ha -1 decreased fruit fresh weight by 11.21 percent. On contrary, the results obtained from this study is higher than the reported value of 127.04 kg N ha -1 and 65 kg P ha -1 with fruit fresh weight of 16.72 t ha -1 [26]. The observed disparity between the results could be explained on the basis of the soil fertility difference and the environmental conditions upon which the plant was grown.…”
Section: Economic Evaluationcontrasting
confidence: 97%
“…Weight of corms plant -1 increased at wider spacing might be due to less competition for nutrients, moisture and light among the plants. Suminarti et al (2016) obtained the highest yield of corms and cormels plant -1 from 60 cm x 40 cm spacing. Sikder et al (2014) also got the maximum and minimum individual corm from 60 cm x 50 cm and 60 x 20 cm spacing, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…The lowest number of secondary corms plant -1 was obtained from S 3 F 2 combination in both the years. Suminarti et al (2016) reported that application of 125 kg N ha -1 and 62 kg K ha -1 gave the highest yield of mukhikachu (16.45 t/ha) and number of corms plant -1 decreased with the increase of plant population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian ini dilaksanakan selama 4 bulan dari bulan April sampai dengan bulan Tingkat ketersediaan N yang sangat rendah berakibat pada rendahnya laju pertumbuhan tanaman (Suminarti et al, 2016). Apabila energi yang tersedia rendah, maka proses pertumbuhan juga terganggu yang selanjutnya akan berdampak pada rendahnya pertambahan ukuran organ tanaman seperti jumlah cabang maupun luas daun (Mohammad et al, 2012).…”
Section: Metode Penelitianunclassified